Rb =
Rk =
AP =
\(a=\dfrac{1}{\sqrt{A}}\)
R10 =
\(R_{10}=\dfrac{\left(a^2-1\right)\cdot R_b\cdot\sqrt{R_k}}{\left(a^2+1\right)\cdot\sqrt{R_k}-2\cdot a\cdot\sqrt{R_b}}\)
R11 =
\(R_{11}=\dfrac{\left(a^2-1\right)\cdot\sqrt{R_b\cdot R_k}}{4\cdot a}\)
R12 =
\(R_{12}=\dfrac{\left(a^2-1\right)\cdot\sqrt{R_b\cdot R_k}}{4\cdot a}\)
R13 =
\(R_{13}=\dfrac{\left(a^2-1\right)\cdot R_b\cdot\sqrt{R_k}}{\left(a^2+1\right)\cdot\sqrt{R_k}-2\cdot a\cdot\sqrt{R_b}}\)

⌂ Index

Verzió: 2024-07-22 ( 2010-07-11 .. 2024-05-13 14:55:29 UTC )